Modelo dinámico y control de simulador de conducción de 2 grados de libertad - Ávalos García, Julio Javier; Izaguirre Castellanos, Eduardo; Hernández Santana, Luis (My University, 2015)
Dynamic modelling is the basic element for controller design of robotics’ mechanisms. In this paper, an effective dynamic equation of a 2 DOF Parallel Driving Simulator Platform has been derived by the Newton-Euler formulation. The proposed model leads to decoupling dynamic characteristics, in which the complexity of the controller design can be significantly reduced. A model-based Computed-Torque Control strategy with a PD Controller in the Cartesian space is implemented in order to obtain the desired performance of the system. The Cartesian control performs an accurate positioning of the end effector, according to the desired task-space specifications. The proposed control strategy is simulated using the MATLAB software package, where simulation results proved that the designed control motion simulator scheme is adequate to performs different driving situations according with the performance specifications of the system.
Keywords: 2-DOF; Espacio Cartesiano; Torque Calculado; Robot Paralelo; Plataforma